Age-related clinical characteristics of children and adolescents with ADHD - De Rossi, Pietro; D’Aiello, Barbara; Pretelli, Italo; Menghini, Deny; Di Vara, Silvia; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Attention deficit hyperactivity disorder (ADHD) has been associated with difficulties in regulating aversion states, high functional impairment, and a high risk of psychopathology across the lifespan. ADHD is clinically heterogeneous, with a wide spectrum of severity and associated symptoms. Clinical characteristics need to be carefully defined in different periods of life as ADHD course, symptoms and comorbidities may fluctuate and change over time. Adolescence usually represents the transition from primary to secondary education, with a qualitative and quantitative change in environmental and functional demands, thus driving symptoms’ change. In order to characterize age-related clinical features of children (<11 years) and adolescents (≥ 11 years) with ADHD, we conducted a naturalistic study on 750 children and adolescents assessed for ADHD at our Neuro-psychiatry Unit over the course of 3 years (2018-2020). We found that ADHD symptoms were significantly higher in children than adolescents, consistent with the developmental trajectory typically described for ADHD-specific symptoms. More importantly, we found worse global functioning, lower adaptive skills, higher levels of anxiety and depressive symptoms, somatic complaints, emotional dysregulation, social problems and aggression in adolescents, despite a lower severity of ADHD-specific symptoms. In conclusion, our study seems to confirm on a large clinical sample that the developmental trajectory of ADHD between childhood and adolescence unfolds through a progressive functional decline, paralleled by an increase in general psychopathology with a fading of ADHD-specific symptoms.